Valor nutritivo de macrófitas aquáticas flutuantes (Eichhornia crassipes, Pistia stratiotes e Salvinia molesta) utilizadas no tratamento de efluentes de aqüicultura - Henry-Silva, Gustavo Gonzaga [UNESP] (2002)
The aim of this study was to evaluate the nutritive value of free-floating aquatic macrophytes, Eichhornia crassipes (Mart.) Solms (Pontederiaceae), Pistia stratiotes (L.) (Araceae) and Salvinia molesta (Mitchell) (Salviniaceae) used in a Nile tilapia (Oreochromis niloticus) waste treatment, and these species biomass potential uses. The vegetal biomass samples were collected from 0.25 m 2 floating squares and divided in aerial and submerse parts, to determine the concentrations of cell wall fraction, soluble carbohydrates, polyphenols, lipids, crude protein and total phosphorus. The higher nutritive value was observed in E. crassipes and S. molesta aerial parts, and in P. stratiotes total biomass, due to their lower cell wall fraction mean rates (60.7; 64.2 and 56.9 % dry mass, respectively) and to the higher rates of: crude protein (10.1; 9.1 and 8.8 % dry mass, respectively), soluble carbohydrates (26.6; 18.7 and 12.4 mg.g -1 dry mass, respectively) and lipids (7.6; 4.5 and 4.4% dry mass, respectively). It may be concluded that P. stratiotes total biomass, and E. crassipes and S. molesta aerial biomass have nutritive values with potential use for ruminant feeding or as ration ingredients.